2018
DOI: 10.1371/journal.pone.0200053
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the active interaction mechanism of phytochemicals withanolide and withanoside derivatives with human serum albumin

Abstract: Withania somnifera (Ashwagandha) is an efficient medicinal plant known in Ayurveda and Chinese medicine since ancient times, whose extracts are consumed orally as food supplement or as a health tonic owing to its several restorative properties for various CNS disorders, inflammation, tumour, stress, rheumatism etc. In this study, we have analyzed the binding interaction of four derivatives of Withania somnifera (Withanolide A, Withanolide B, Withanoside IV and Withanoside V) with HSA because of their important… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…These contradictory findings may be explained by a different sensibility of the cell types used. Moreover, the binding to soluble proteins within PRP, such as human serum albumin (HSA) or immunoglobulins, may have interfered with the uptake of frondoside A into platelets [22]. Therefore, higher concentrations of the compound were needed to exert detectable antithrombotic effects in our experimental setting.…”
Section: Discussionmentioning
confidence: 99%
“…These contradictory findings may be explained by a different sensibility of the cell types used. Moreover, the binding to soluble proteins within PRP, such as human serum albumin (HSA) or immunoglobulins, may have interfered with the uptake of frondoside A into platelets [22]. Therefore, higher concentrations of the compound were needed to exert detectable antithrombotic effects in our experimental setting.…”
Section: Discussionmentioning
confidence: 99%
“…In silico results of our study also corroborate with the one performed by Singh et al [43] in which withanolide A from Withania somnifera (L.), with neuropharmacological activity, presented high PPB, passive permeability and a fast and wide distribution kinetics in vitro. Also, Dubay et al [44] demonstrated that withanolides and withanosides of W. somnifera have a strong binding to serum albumin. In addition, further structure-based drug design with withanolides is required.…”
Section: Discussionmentioning
confidence: 99%
“…For example, four extracts from Withania somnifera were interacted with human serum albumin to explore their pharmaceutical properties. AFM showed that the derivatives could bind to human serum proteins resulting in greater stability, thus enhancing the scope for development of such steroidal derivatives (Dubey, Kallubai, Sarkar, & Subramanyam, 2018). AFM has been used to explore the interaction between marine bacterial GY785 exopolysaccharide and transforming growth factor-β1, showing that the interaction can promote the differentiation of some tissues.…”
Section: Interaction Phenomena and Complexesmentioning
confidence: 99%